John J. Bayer papers - Bayer, John J., 1887-1967.
Correspondence, diaries (1928-1930), autographs, newspaper clippings, and a photograph album pertaining to Bayer's service as a member of the scientific team on the supply ship City of New York during the first Byrd Antarctic Expedition (1928-1930). Correspondents include Richard Evelyn Byrd and Franklin D. Roosevelt.
Naval officer, engineer, and explorer. Also known as Teddy Bayer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Byrd, Richard Evelyn, -- 1888-1957 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; City of New York (Ship); Antarctica -- Discovery and exploration; Engineers; Explorers; Naval officers